1981
DOI: 10.1159/000182136
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Type Glomerulonephritis Induced in the Brown-Norway Rat with Mercury-Containing Pharmaceutical Products

Abstract: It has been shown that Brown-Norway rats develop an immune-type glomerulonephritis after treatment with various mercury-containing drugs. Anti-GBM antibodies were involved, at least in some animals. This glomerulonephritis induced a proteinuria. Strong evidence is given, suggesting that most mercury compounds, some of which, such as mercurial antiseptics, are widely used, could induce an immune-type glomerulonephritis. The question therefore arises, whether these drugs can be used any longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The systemic nature of the HgCl, induced disease in experimental animals has been documented in a number of reports. The gastrointestinal tract was also among the tissues involved (2,4, 6,8,12,13). It seemed especially interesting to determine if the intestinal involvement in BN rats treated orally differed from that of i.m.-injected rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systemic nature of the HgCl, induced disease in experimental animals has been documented in a number of reports. The gastrointestinal tract was also among the tissues involved (2,4, 6,8,12,13). It seemed especially interesting to determine if the intestinal involvement in BN rats treated orally differed from that of i.m.-injected rats.…”
Section: Discussionmentioning
confidence: 99%
“…Druet et a1 produced renal lesions in BrownNorway (BN) rats by applying mercury-containing drugs to the skin, on wounds, into the vagina, and by mouth. Their findings provided strong evidence against the use of mercury-containing ointments and antiseptics (8).…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have shown that treatment with mercury in its various chemical forms, using different routes of administration (subcutaneous injection, oral ingestion, inhalation), results in autoimmune responses to a variety of antigens (7)(8)(9)(10). Relatively low doses of mercury have been found to be effective in both rats and mice; for example, the immunotoxic effects of If -HgCI2 occur in BN rats at doses (3-25 ,g/100 g body weight) that are much lower than those causing the common nephrotoxic effects (11,12,Bigazzi et al, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…Various other inbred rat strains (Lewis, Wistar AG, August, PVG/c) do not produce such antibodies under the same experimental conditions [37]. The immune reaction in mercury-sensitive Brown Norway rats is accompanied by an autoimmune renal disorder, identified as a membranous glomerulonephropathy [14,38,39]. After inhalation of mercury vapor (0.3-1.0 mg Hg/m 3 air for up to 10 weeks), mercury-susceptible mouse strains produce antinuclear antibodies, followed by deposition of immunocomplexes in the glomerulus [40].…”
Section: Autoimmunity In Mercury-sensitive Rodent Strainsmentioning
confidence: 99%